Postsynaptic protein synthesis is required for presynaptic enhancement in persistent forms of long-term potentiation - Johnstone, Victoria P.; Raymond, Clarke R. (Frontiers in Synaptic Neuroscience, 2013)
Long-term potentiation (LTP) in the hippocampus is a fundamental process underlying learning and memory in the brain. At CA3-CA1 synapses, three discrete forms of LTP (LTP1, 2 and 3) have been differentiated on the basis of their persistence, maintenance mechanisms, Ca2+ signaling pathways, expression loci, and electrophysiological requirements. We previously showed that LTP2 and LTP3 involve a presynaptic expression component that is established in a translation-dependent manner. Here we investigate the locus of translation required for presynaptic expression. Neurotransmitter release rate was estimated via FM 1-43 destaining from CA3 terminals in hippocampal slices from male Wistar rats (6-8 weeks). Destaining was measured at sites making putative contact with CA1 dendritic processes in stratum radiatum that had been filled with a membrane impermeable translation inhibitor and a fluorescent indicator. Our results suggest that inhibition of postsynaptic translation eliminates the enhanced release ordinarily observed at 160 min post LTP induction, and that this effect is limited to sites closely apposed to the filled postsynaptic cell. We conclude that postsynaptic translation is required for the presynaptic component of LTP2 and LTP3 expression. These data considerably strengthen the mechanistic separation of LTP1, 2 and 3 and provide evidence for an expanded repertoire of communication between synaptic elements.